2022
DOI: 10.32674/jcihe.v14i4.4429
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on International Students in a Public University in the United States: Academic and Non-academic Challenges

Abstract: The COVID-19 pandemic has substantially impacted higher education. The unexpected move to online learning and support services have created many challenges.  International students, who often are unfamiliar with the culture and norms of American higher education, have been particularly disadvantaged. Analyzing data received through an online survey, researchers identified the top five academic and non-academic challenges faced by international students during the pandemic, and their use of support services to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Chinese international students will feel that it's tough for them to find a study group and be left behind by others. According to a study centering on the impact of the pandemic, the researchers pointed out that most international students lack the opportunities to interact with their classmates, and only 60% of the students reported that they adapt well to online learning [6]. The lack of communication is supposed to lead to different extents of negative impacts on different kinds of majors.…”
Section: Academic-related Issuesmentioning
confidence: 99%
“…Chinese international students will feel that it's tough for them to find a study group and be left behind by others. According to a study centering on the impact of the pandemic, the researchers pointed out that most international students lack the opportunities to interact with their classmates, and only 60% of the students reported that they adapt well to online learning [6]. The lack of communication is supposed to lead to different extents of negative impacts on different kinds of majors.…”
Section: Academic-related Issuesmentioning
confidence: 99%
“…Academic libraries play a crucial role in assisting international students with transitioning to an online learning environment during the pandemic (Zhao et al, 2022). Martirosyan et al (2022) surveyed international students at an American public university concerning their academic and non-academic challenges during the COVID-19 pandemic. Their study revealed that international students recognized the importance of library services and made use of them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2022). Martirosyan et al . (2022) surveyed international students at an American public university concerning their academic and non-academic challenges during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%